Analysis of Invasiveness of Pneumococcal Serotypes and Clones Circulating in Portugal before Widespread Use of Conjugate Vaccines Reveals Heterogeneous Behavior of Clones Expressing the Same Serotype - Sá-Leão, Raquel (American Society for Microbiology, 2011)
To estimate the invasive disease potential of serotypes and clones circulating in Portugal before extensive use of the seven-valent pneumococcal conjugate vaccine, we analyzed 475 invasive isolates recovered from children and adults and 769 carriage isolates recovered from children between 2001 and 2003. Isolates were serotyped and genotyped by pulsed-field gel electrophoresis, and a selection of isolates were also characterized by multilocus sequence typing. We found that the diversities of serotypes and genotypes of pneumococci responsible for invasive infections and carriage were identical and that most carried clones could also be detected as causes of invasive disease. Their ability to do so, however, varied substantially. Serotypes 1, 3, 4, 5, 7F, 8, 9N, 9L, 12B, 14, 18C, and 20 were found to have an enhanced propensity to cause invasive disease, while serotypes 6A, 6B, 11A, 15B/C, 16F, 19F, 23F, 34, 35F, and 37 were associated with carriage. In addition, significant differences in invasive disease potential between clones sharing the same serotype were found among several serotypes, namely, 3, 6A, 6B, 11A, 14, 19A, 19F, 22F, 23F, 34, and NT. This heterogeneous behavior of the clones was found irrespective of the serotype's overall invasive disease potential. Our results highlight the importance of the genetic background when analyzing the invasive disease potential of certain serotypes and provide an important baseline for its monitoring following conjugate vaccine use. Continuous surveillance should be maintained, and current research should focus on uncovering the genetic determinants that contribute to the heterogeneity of invasive disease potential of clones sharing the same serotype.